Lithium Metal Batteries Operating at Room Temperature Based on Different PEO-PVdF Separator Configurations - Sannier, L.; Bouchet, R.; Santinacci, L.; Grugeon, S.; Tarascon, J.-M. (Journal of the Electrochemical Society, 2004)
Gel polymer electrolyte (GPE) membranes based on two polymers, the polyethylene oxide (PEO) and a copolymer of polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), and a plasticizer, the dibutylphthalate (DBP), were elaborated in two ways. First, the polymers and the plasticizer were mixed together to obtain a single membrane. Second, a bilayer separator membrane was made by adjunction, through lamination, of a DBP plasticized PVdF-HFP film and a homemade DBP-PEO thin film. The physicochemical properties of the gels were analyzed. AC impedance spectroscopy was carried out on symmetric Li/GPE/Li cells using either the single layer or bilayer membrane as a function of aging (isothermal at 20 and 70DGC), temperature (-40 to 70DGC), and finally, galvanostatic cell polarization. Both GPE membranes exhibit high ionic conductivities, but the most spectacular result was the measured decrease in the interface resistance, indicative of a deep modification of the interface Li/GPE when the cells were polarized. Aside from having a good interface with the Li metal electrode, such membranes were also shown to form good interfaces with the cathode because assembled Li/GPE/Li4Ti5O12 flat cells were able to sustain, at room temperature, more than 80% of their initial capacity for more than 300 cycles.